Optimization Of Portofolio Using NSGA-II Between Conventional and Shariah Stocks in Turkey - Marselly Dewa Utama; Dwi Eko Waluyo; Ana Kadarningsih; Pradana Jati Kusuma (Journal of Management Economics and Financial Accounting, 2026)
This study addresses the critical need for effective portfolio optimization in investment decision-making, particularly given the increasing complexity of stock types and classifications, such as conventional and Sharia-compliant indices in Turkey. This research aims to: (1)identify the optimal stock combinations across conventional, sharia, indexed in both, and combined, (2) analyze their efficient frontiers, and (3) compare performance ratios (Sharpe, Sortino, Omega) and expected returns for each group. Using a quantitative descriptive method, this study applies the Non-Dominated Sorting Genetic Algorithm II (NSGA-II) to optimize portfolios based on historical daily closing prices of BIST100 and KATILIM50 index stocks from January 3, 2022, to December 30, 2025. This finding indicates a trade-off between risk and return across all portofolio groups. A conventional portfolio alone offers the highest expected returns but also higher risk, while a Sharia-compliant portfolio alone provides lower returns and risk, suitable for investors who prioritize Sharia compliance. The combined portfolio group showed superior risk-adjusted performance, particularly in the Sharpe and Omega ratios, indicating better diversification potential with lower risk and competitive returns. Meanwhile, groups that are listed on both indices performed moderately. This research provides valuable academic references for technical and fundamental analysis in portfolio management, emphasizing that optimal portfolio selection is highly dependent on investor risk preferences.